Into the 20th century - Potts, Ian.; WNET (Television station : New York, N.Y.).
Covers the work of the fauves, the cubists, the international style, and the surrealists. Discusses how these movements relate to modern life.
An Annenberg/CPB project.
VHS.
Host, Michael Wood.
Keywords: Art, Modern -- 20th century